Gamification in sport apps: the determinants of users' motivation - Paula Bitrián; Isabel Buil; Sara Catalán (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose Gamification is a tool with great potential to motivate individuals to increase their physical activity. That is why sport apps for mobile devices, such as Nike+ or Strava, have integrated game elements. There is, however, little evidence of gamification's effectiveness in this field. Therefore, the aim of the present study is to analyze the impact of game elements included in gamified sports' apps on the satisfaction of basic psychological needs (i.e. competence, autonomy and relatedness). Similarly, the research analyzes the impact of these needs on autonomous motivation. Design/methodology/approach To achieve these goals, data were collected from users of gamified sport apps, using an online questionnaire. The data were analyzed using partial least squares structural equation modeling. Findings The results showed that interaction in the app with achievement-related game elements satisfied the needs for competence, autonomy and relatedness; social-related elements satisfied the need for relatedness; and immersion-related elements satisfied the needs for competence and autonomy. Similarly, satisfaction of the needs for autonomy and relatedness while using the app is crucial to experience autonomous motivation. Practical implications The findings of this study provide guidelines for practitioners and app developers. Originality/value Based on self-determination theory, the paper provides new insights into the relationship between game elements included in sport apps and individuals' basic psychological needs and motivation.
Keywords: 650; Bitcoin; Economic policy uncertainty; Safe-haven asset; Speculative asset